Financial Prospects of Porang Cultivation in East Lombok Regency, Indonesia - Rini Endang Prasetyowati; Idiatul Fitri Danasari; Murah Murah; Muhammad Joni Iskandar; Rizal Ahmadi; Rio Akbar Rahmatullah (Jurnal Social Economic of Agriculture, 2023)
Porang or Amphophallus, locally known as porang or suweg, is a plant widely cultivated using traditional ecological knowledge in East Lombok Regency, West Nusa Tenggara Province. However, the increasing number of farmers in several villages in East Lombok Regency is still not followed by knowledge and skills in accordance with good agricultural practices. This study investigated the prospects of porang cultivation in East Lombok Regency, West Nusa Tenggara Province. The research used quantitative methods through a feasibility study approach on financial aspects. Data were collected by FGDs and interviews with 25 farmers, including key informants who were purposively selected considering having expertise and knowledge about porang in East Lombok Regency. The results showed that the prospect of porang through financial aspects in East Lombok Regency is prospective and profitable. This is evidenced by the R/C ratio of 2.1, the B/C ratio of 1.01, and the BEP of Rp27,471,818/Ha.